2010
DOI: 10.1038/ijo.2010.253
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and reduced body temperature in dogs

Abstract: Background: Industrialized nations are currently experiencing an obesity epidemic, the causes of which are not fully known. One possible mechanism of enhanced energy efficiency that has received almost no attention is a reduction in the metabolic cost of homeothermy, which could be achieved by a modest lowering of body core temperature. We evaluated the potential of this obesity-inducing mechanism in a canine model of the metabolic syndrome. Methods: We compared the rectal temperature of lean dogs and obese do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…Piccione et al (17) did observe breed differences with diurnal change in daytime and nighttime BT, which, as stated above, is sensitive to masking because of physical activity or environmental stimuli. Thus in the current study, the movement of the dogs in the AM to obtain the measurements may have influenced the morning BTs that was sustained throughout the day with subsequent measurement collection.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Piccione et al (17) did observe breed differences with diurnal change in daytime and nighttime BT, which, as stated above, is sensitive to masking because of physical activity or environmental stimuli. Thus in the current study, the movement of the dogs in the AM to obtain the measurements may have influenced the morning BTs that was sustained throughout the day with subsequent measurement collection.…”
Section: Discussionmentioning
confidence: 79%
“…This study also reports observations of breed size differences in BT with all three methods resulting in Labrador Retrievers having a higher BT compared to Beagles, with no observed interaction between breed and time in the sedentary portion of the study. Other studies have reported an opposite observation of small breed dogs having a higher BT compared to larger breed dogs (17). It is unclear of the discrepancy between breed sizes between this study and others.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…), precluding the possibility that decreased SNS activity contributes to obesity, but consonant with a diminished thermogenic response to sympathetic stimulation . Obese dogs have recently been shown to have lower body temperatures as compared with lean dogs of the same body mass .…”
Section: Core Temperature and Obesitymentioning
confidence: 99%